Impaired auditory evoked potentials and oscillations in frontal and auditory cortex of a schizophrenia mouse model. (17th August 2016) - Shahriari, Yalda; Krusienski, Dean; Dadi, Yamini Sureka; Seo, Misun; Shin, Hee-Sup; Choi, Jee Hyun
Abstract: Objectives : In patients with schizophrenia, γ-band (30–70 Hz) auditory steady-state electroencephalogram responses (ASSR) are reduced in power and phase locking. Here, we examined whether γ-ASSR deficits are also present in a mouse model of schizophrenia, whose behavioural changes have shown schizophrenia-like endophenotypes. Methods : Electroencephalogram in frontal cortex and local field potential in primary auditory cortex were recorded in phospholipase C β1 (PLC-β1) null mice during auditory binaural click trains at different rates (20–50 Hz), and compared with wild-type littermates. Results : In mutant mice, the ASSR power was reduced at all tested rates. The phase locking in frontal cortex was reduced in the β band (20 Hz) but not in the γ band, whereas the phase locking in auditory cortex was reduced in the γ band. The cortico-cortical connectivity between frontal and auditory cortex was significantly reduced in mutant mice. Conclusions : The tested mouse model of schizophrenia showed impaired electrophysiological responses to auditory steady state stimulation, suggesting that it could be useful for preclinical studies of schizophrenia".